DA OBJEÇÃO AO RECONHECIMENTO: uma análise da política eclesiástica da Assembleia de Deus brasileira com respeito à educação teológica formal (1943-1983) - Gomes, José Ozean (2013)
This text is a result of a research from a sociological and historical perspective about the ecclesiastical policy of the Brazilian Assemblies of God regarding the pastoral and theological formation of its ministers. The aim of this research was to understand how a shift in the Assembleian leadership happened as far as formal theological education is concerned, as they started to admit it as a requisite for pastoral ministry. This research starts in the year 1943 as in that year the first official discussions about formal theological teaching had place in the Assemblies of God, and it was decided not to create theological seminaries. The shift happened slowly, due to a several facts, such as the decreasing of influence of Swedish missionaries, the creation of a publishing house, the coming of American missionaries and the rising of pastors who defended a formal theological education. Forty years later, in 1983, the General Convention of the Assembleyan leaders decided for recommending theological formation as a requirement for pastoral ministry. The methodology used in this thesis was bibliographical research. In order to do an explanatory study it was done a research on historical data from the official newspapers of the AoG, and also of documents that speak about the subject of this research.